Interaction of Vibration and Air Flow-Accelerating Droplet Emission from the Gas Diffusion Layer of Proton Exchange Membrane Fuel Cell - Sitong Chen; Xueke Wang; Tong Zhu; Xiaofeng Xie (International Journal of Photoenergy)
In order to explore the influence of vibration that the vehicles are often subjected on water management of PEMFC, the dynamic characteristics of vibrating droplet on gas diffusion layer (GDL) surface were investigated through a high-speed image technology. The operating condition of vertical and horizontal excitations separately or coupled with air flow under different frequencies and amplitudes are applied on the substrate, so that the laws for the transition from Wenzel-Cassie regime to Cassie regime and the contact angle, the deformation rate for the width and height are obtained. It is observed that the wetting diameter of the droplet is smaller than the initial value under vertical vibration, making it easier for the gas to discharge the water droplets from the PEMFC. For the horizontal excitation, the droplet is pulled apart when the applied energy exceeded the cohesive energy at elevated frequency and amplitude. Moreover, as to the interaction of vibration and air flow, the droplet was more likely to move forward under the gas-driven force.